Study On The Application Of The Articulated Concrete Block Mattresses Method As Subsea Pipeline Protection (Collaborate Engineering Daily Book Series, 2023)
Subsea pipe installations are installed on the seabed with a particular security system so that the pipes will not shift from their location due to wave pressure, tidal currents and ground movements. The underwater pipes are installed so that they follow the seabed's contour with an installed length of tens of kilometres, which routinely carries feed intake and other process materials. Hence, the existence of this underwater pipe is essential. Some of the problems faced in underwater pipes include damage to underwater pipes due to shifting and kinking, pipes hitting ship anchors, and pipes being dragged by ship anchors so that they are damaged and broken. This incident resulted in disruption and cessation of company operations. This problem requires further investigation to find out the factors and causes of the incident in order to find an effective solution. Articulated Concrete Block Mattresses (ACBM) are artificial concrete blocks in a rectangular shape which will be installed regularly on underwater pipes (SPL) and between one block and another concrete block connected with polypropylene ropes. ACM adjusts its geometry to suit the structure and adapts to undulations in the river/seabed (e.g. due to scouring). From the description of the research results and discussion of the research results, several things can be concluded as follows: The hydrodynamic coefficient of the ACBM can be obtained using an experimental test process, namely the direct pull test, which will produce coefficient values ​​that need to be validated by predicting the cell strength load and crisis speed with maximum error agreement. by 8.3% in five varied tests. Moreover, it was obtained using a numerical study that simulates pipes protected with ACBM in two conditions: regular waves in deep water and breaking waves in shallow water. Moreover, these two studies concluded that the drag and lift coefficients on pipes protected with ACBM were smaller than those on pipes that were not protected.
Keywords: Articulated Concrete Block Mattresses, Submarine Pipeline